Under Whose Umbrella? The European Security Architecture - Teodor Lucian Moga (CES Working Papers, 2010)
The tragic events which occurred during the `90s in the Balkans have reiterated the need for the European Union (EU) to assume a much more assertive role in managing security concerns in Europe, including the development of European defence capabilities. In 1998, at Saint Malo, Tony Blair and Jacques Chirac launched the European Security and Defence Policy (ESDP). This project has been generated due to the EU's need to adopt a strategic framework within which to develop a global defence and security component, as well as due to a growing necessity for the EU to contribute effectively to North Atlantic Treaty Organization (NATO) and United Nations (UN) efforts of conducting defence, international crisis management and peacekeeping operations at an international level in conflict-prone areas. In recent years, ESDP has undergone a spectacular evolution, being now among the major issues discussed in Brussels. However, the creation of the ESDP has been greeted with caution by some NATO members being perceived primarily as a threat to the integrity of the North Atlantic Treaty Organization. The purpose of this paper is to examine the difficulties the ESDP has encountered since its inception and also to what extent it has affected the EU-NATO and the EU-US nexus.
Keywords: 330; European Union; European Security and Defence Policy; North Atlantic Treaty Organization; European security architecture